STUDI LITERATUR DAMPAK MIKROPLASTIK TERHADAP LINGKUNGAN - NI MADE NIA BUNGA SURYA DEWI (SOSIAL SAINS DAN TEKNOLOGI, 2022)
Plastic take hundreds to thousands of years to decompose. During this time, plastic has created serious problems for the environment. Once plastic waste is left in the environment, it will be exposed to natural elements, such as solar radiation, wind, or rain. In turn, the plastic will break down over time until the are invisible. In general, the plastic decomposition process takes place very slowly and takes hundreds of year for the      plastic to be degraded into microplastics (MP) and nanoplastics (NP) through various physical, chemical and biological processes. MP is defined as small pastic particles measuring < 5 mm  and having a very large negative impact on the environment. MP can be found anywhere, even in the deepest seas of the Earth. But in reality MP is all around us and so dangerous. The problem of environmental damage due to waste is always interesting to discuss and has also become a global issue and the magnitude of the impact caused by plastic has become a serious problem that can’t be ignored. Plastic which was originally a useful and versatile object has now turned into a threat to the survival mandkind